Middle East Oil Show 2003
DOI: 10.2118/81462-ms
|View full text |Cite
|
Sign up to set email alerts
|

Water Injection and Water Flooding Under Fracturing Conditions

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractWith the realization that water injection is generally taking place under fracturing conditions, tools capable of better modelling fractured injection and its impact are being developed. Models integrating rock (fracture) mechanics and traditional reservoir simulation are now applied to water injection projects with a number of applications in the Middle East. Fracture dimensions are a key input to those models. Monitoring techniques to track the evolution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 5 publications
0
6
0
1
Order By: Relevance
“…Noirot et al demonstrated injection-related rock fracturing using downhole microseismic data from water disposal wells in deep geologic formations. They developed analytical and numerical models to investigate the interaction between pressure buildup and mechanical integrity of the host formation and caprock [29]. Using numerical simulation models, they designed a safe injection process by considering the acceptable limit of injection pressure increase due to caprock integrity and formation fracturing.…”
Section: Research Gaps and Objectivesmentioning
confidence: 99%
“…Noirot et al demonstrated injection-related rock fracturing using downhole microseismic data from water disposal wells in deep geologic formations. They developed analytical and numerical models to investigate the interaction between pressure buildup and mechanical integrity of the host formation and caprock [29]. Using numerical simulation models, they designed a safe injection process by considering the acceptable limit of injection pressure increase due to caprock integrity and formation fracturing.…”
Section: Research Gaps and Objectivesmentioning
confidence: 99%
“…The efficiency of waterflooding carried out to increase oil recovery from hydrocarbon-bearing rocks is predicated in part on the initiation and propagation of hydraulic fractures at injection wells to ensure a more efficient sweep of the reservoir. [1][2][3] These fracture allow the injected water to leak through the crack surfaces, which eventually leads to the establishment of a quasi-linear flow pattern around the borehole-fracture system.…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of waterflooding carried out to increase oil recovery from hydrocarbonbearing rocks is predicated in part on the initiation and propagation of hydraulic fractures at injection wells to ensure a more efficient sweep of the reservoir [Sharma et al, 2000, van den Hoek and Mclennan, 2000, Noirot et al, 2003. These fracture allow the injected water to leak through the crack surfaces, which eventually leads to the establisment of a quasi-linear flow pattern around the borehole-fracture system.…”
Section: Introductionmentioning
confidence: 99%